Mode of Imaging Study and Endovascular Therapy for a Large Ischemic Core: Insights From the RESCUE-Japan LIMIT - Fumihiro Sakakibara; Kazutaka Uchida; Shinichi Yoshimura; Nobuyuki Sakai; Hiroshi Yamagami; Kazunori Toyoda; Yuji Matsumaru; Yasushi Matsumoto; Kazumi Kimura; Reiichi Ishikura; Manabu Inoue; Kumiko Ando; et al. (Journal of Stroke, 2023)
Background and Purpose Differences in measurement of the extent of acute ischemic stroke using the Alberta Stroke Program Early Computed Tomographic Score (ASPECTS) by non-contrast computed tomography (CT-ASPECTS stratum) and diffusion-weighted imaging (DWI-ASPECTS stratum) may impact the efficacy of endovascular therapy (EVT) in patients with a large ischemic core. Methods The RESCUE-Japan LIMIT (Recovery by Endovascular Salvage for Cerebral Ultra-acute Embolism Japan–Large IscheMIc core Trial) was a multicenter, open-label, randomized clinical trial that evaluated the efficacy and safety of EVT in patients with ASPECTS of 3–5. CT-ASPECTS was prioritized when both CT-ASPECTS and DWI-ASPECTS were measured. The effects of EVT on the modified Rankin Scale (mRS) score at 90 days were assessed separately for each stratum. Results Among 183 patients, 112 (EVT group, 53; No-EVT group, 59) were in the CT-ASPECTS stratum and 71 (EVT group, 40; No-EVT group, 31) in the DWI-ASPECTS stratum. The common odds ratio (OR) (95% confidence interval) of the EVT group for one scale shift of the mRS score toward 0 was 1.29 (0.65–2.54) compared to the No-EVT group in CT-ASPECTS stratum, and 6.15 (2.46–16.3) in DWI-ASPECTS stratum with significant interaction between treatment assignment and mode of imaging study (P=0.002). There were significant interactions in the improvement of the National Institutes of Health Stroke Scale score at 48 hours (CT-ASPECTS stratum: OR, 1.95; DWIASPECTS stratum: OR, 14.5; interaction P=0.035) and mortality at 90 days (CT-ASPECTS stratum: OR, 2.07; DWI-ASPECTS stratum: OR, 0.23; interaction P=0.008). Conclusion Patients with ASPECTS of 3–5 on MRI benefitted more from EVT than those with ASPECTS of 3–5 on CT.